Enterprise governance : driving enterprise performance through strategic alignment - Vagadia, Bharat (Heidelberg : Springer, 2013)
This book is written for business leaders and those that govern organisations. All high performing organisations excel in achieving 7 organisational outcomes: Accountability, Awareness, Adaptability, Agility, Alignment, Action and Achievement. The enterprise governance framework must deliver on these 7 As through penetrating and integrating three organisational governance layers to drive high performance. These include: corporate governance, strategic governance and operational governance. The book unifies traditional corporate governance, leadership, and strategic management processes, whilst seeking to understand what actually happens on the ground to keep the organisation working and delivering ongoing value to its stakeholders. It synthesises these separate streams into a unified enterprise governance framework, posing some challenging questions whilst providing clear insight into how you implement enterprise governance: something that helps deliver on the 7 As and ultimately high performance. This book will be a great asset for various stakeholders, including business leaders, NGOs, not-for-profit entities or any other form of organisations that wishes to prosper over the longer term.
A New Approach and Model for Organisational Governance -- Delivering High Performance Organisations Through Enterprise-Wide Governance and Strategic Leadership -- Operational Governance -- Strategic Governance -- Corporate Governance -- Joint Governance -- Systematising Enteprise Governance -- Annex: A Summary of the Corporate Governance Requirements of Different Countries.
Includes bibliographical references.
Keywords: Industrial management; Organizational behavior; Strategic planning; Electronic books